An Exploratory Study of Managerial Practices in the Arabian Gulf Region - Al-Jafary, Abdulrahman; Hollingsworth, A. T. (Journal of International Business Studies, 1983)
This study determined the management system [Likert and Likert 1976] operating in 10 organizations in the Arabian Gulf region and correlated the system with the resultant effectiveness of these organizations. Managers in the region operated in a Management System 3 mode, but at a lower participatory level than desired by managers and at a lower level than their American counterparts. Effectiveness was found to be related to the operative management system; organization climate was the most potent determinant of effectiveness.